THE EFFECT OF CORIANDER LEAF EXTRACT TOWARDS KIDNEY HISTOPATHOLOGICAL FEATURES ON WISTAR RAT INDUCED BY ORALLY ADMINISTERED MERCURY - Manda Petrina; Ika Pawitra Miranti; Nani Maharani; Intan Rahmania Eka Dini (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Mercury’s a toxic heavy metal that damages the kidney through generation of Reactive Oxygen Species (ROS). Previous study has established that coriander leaves contained high level of antioxidants. However, there hasn’t been any experiment that examined renoprotective effect of coriander leaf extract toward the kidney of Wistar rat induced with orally administered mercury.Objective: To examine the nephroprotective activity of coriander leaf extract towards Wistar rat’s proximal tubules induced with orally administered mercuryMethods: : Experimental study with post test only control group design using 20 male Wistar rats divided randomly into 4 groups as samples. Group K0 without treatment, Group K(-) was administered 10 mg/ kgBW mercury chloride orally, Group P1 was administered 10 mg/kgBW mercury chloride and 100 mg/kgBW coriander leaf extract orally, and Group P2 was administered 10 mg/kgBW  mercury chloride and 200 mg/kgBW coriander leaf extract orally. The study was carried for 14 days after which the kidneys were examined microscopically.Results: The mean values for damaged proximal tubules were as follows: group K0 2,44±1,19; group K(-) 4,76±3,77; group P1 4,52±2,18; group P2 2,60±1,38. Mann-Whitney test showed significant differences between group K(-)>K0 (p=0,009); group P1>K0 (p=0,001); group P2<K(-) (p=0,015); group P1>P2 (p=0,001). Insignificant differences were found between group P2> K0 (p=0,936) and group P1<K(-) (p=0,579).Conclusion: Coriander leaf extract could reduce the number of damaged proximal tubules from mercury ingestion, with dose of 200 mg/kgBW showing better result than 100 mg/kgBW.Keywords: antioxidants, coriander leaf, kidney, mercury